Knowledge of the care of wounded patients: evidence of validity of an instrument - Eurides Araújo Bezerra de Macedo; Camylla Cavalcante Soares de Freitas; Alessandra Justino Dionisio; Gilson de Vasconcelos Torres (Associação Brasileira de Enfermagem, 2019)
ABSTRACT Objective: to present evidence of validity of an instrument aimed at evaluating the knowledge of nursing students about the care of the wounded patient, according to the difficulty and discrimination indexes of the items. Method: methodological study conducted in a nursing higher education institution with 117 undergraduate students and 38 professionals from a research group with experience in the area of wounds. For data collection, a questionnaire with 10 multiple choice questions was applied before and after classes on wounds. Results: most of the questions presented low level of difficulty and inefficient discrimination index, requiring a revision of the instrument. After two review stages, the difficulty and discrimination indexes of the instruments improved. Conclusion: an instrument with better evidence of validity was obtained. However, it still requires refinement for later revalidation in the same population.